Pharmacological and Non-Pharmacological Interventions for the Treatment of Obesity: A Review of Guidelines and Clinical Trials (2020–2025) - Gęborys, Anna; Wojcieszak, Maja; Dąbrowska, Julia; Miazga, Dominika; Maziarczyk, Alicja; Lambach, Jakub; Kutnik, Kacper; Kania, Joanna; Woźnica, Weronika; Białogłowski, Michał (Journal of Education, Health and Sport, 2026)
Background. Obesity is a long-term, relapsing condition that necessitates lifelong treatment.The years 2020 through 2025 signify a paradigm shift in obesity medicine with the departure from behavior-centric models towards neurohormonal interventions, led by the approval of high-efficacy incretin-based therapies. Aim. To review current clinical practice guidelines and pivotal randomized controlled trials(RCTs)published between Jan 1, 2020 and Jan 1, 2025, regarding the efficacy, safety, and cardiovascular outcomes of pharmacological and non-pharmacological treatments. Material and Methods. A comprehensive search of the literature was conducted in PubMed/MEDLINE, Embase, and Cochrane Library databases covering the period from Jan 1, 2020 to Jan 1, 2025. The review focused on Phase 3 RCTs, meta-analyses, and consensus guidelines from major medical societies (ADA, EASO, AACE, ASMBS).Key search terms included obesity, GLP-1 receptor agonists, semaglutide, tirzepatide and lifestyle intervention. Result. Lifestyle treatment (Medical Nutrition Therapy and physical activity)continues to be the cornerstone of therapy but is associated with limited long-term effectiveness as monotherapy due to metabolic adaptation.In stark contrast, new pharmacologic therapies have transformed the standards of care. Semaglutide 2.4 mg(STEP trials)demonstrated a mean weight loss of 14.9%, while tirzepatide (SURMOUNT trials) achieved up to 20.9% mean weight loss, with more than 30% of patients achieving results comparable to bariatric surgery.The SELECT trial(2023)further demonstrated that GLP-1 receptor agonists decreased MACE by 20% in patients with obesity and established cardiovascular disease. Conclusion. Multimodal treatment is required for modern obesity care.Although lifestyle modification remains an essential component of metabolic care, next-generation pharmacotherapy is increasingly recommended for patients with a BMI ≥30 kg/m²(or ≥27 kg/m² with comorbidities)to address physiological set points.